Structural response of abdominal muscles to six weeks of strengthening training in women with diastasis recti - Fatemeh Izadi; Minoo Khalkhali Zaviyeh; Alireza Akbarzadeh Baghban (Mashhad University of Medical Sciences, 2018)
Introduction: Diastasis recti is defined as separation of the two bellies of the rectus abdominis muscles more than 2 to 2.7 cm which could affect the abdominal activities such as breathing, urination and delivery, and may change the body posture and  make the lumbar and sacral regions susceptible to injury.  Regarding the importance of therapeutic exercises in treatment of diastasis recti, this study was performed with aim to investigate the effect of strengthening training of oblique muscles on inter-recti distance and thickness of abdominal muscles in women with diastasis recti. Methods: This randomized controlled clinical trial was performed on 32 women with diastasis recti and at least six months since delivery who referred to physiotherapy center of Hazrate Zainab clinic of Noor city in 2017. The inter recti distance and the thickness of the abdominal muscles before the intervention was determined by ultrasound at rest. In the intervention group, strengthening training of oblique muscles was conducted at home for six weeks .The control group did not do any specific exercises. After six weeks, the inter recti distance and abdominal muscle thickness were measured again using ultrasound at rest. Data was analyzed by SPSS software (version 22) and t-test, Mann-Whitney, Paired t test, and Wilcoxon test. Results: The inter recti distance after six weeks of training in the intervention group showed a significant decrease (p=0.001 and p=0.03 in upper and lower umbilicus). The thickness of the oblique muscles and the transverse abdominal muscles in both side was significantly increased after six weeks in the intervention group (p<0.05). In the control group, there was no significant change in the inter recti distance and the thickness of the abdominal muscles. Conclusion: Strengthening training of oblique muscles reduces inter-recti distance and increase the thickness of the oblique muscles as well as the transverse abdominal muscles in women with diastasis recti.